Development of Scratch-Based Srikandi Media for Indonesian Cultural Heritage in Elementary School: A Preliminary Study - Salzabila, Putri Alicia; Fakhriah, Fina; Fajrie, Nur (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This research aims to develop Scratch-based learning media called SRIKANDI on IPAS material for grade IV elementary school, especially Chapter 6,